3,6-Dibromo-9-(4-bromobenzyl)-9H-carbazole - Cui, Jian-lan (International Union of Crystallography, 2009)
The title compound, C(19)H(12)Br(3)N, was synthesized by N-alkylation of 1-bromo-4-(bromomethyl)benzene with 3,6-dibromo-9H-carbazole. There are two unique molecules in the asymmetric unit. The carbazole ring system is essentially planar, with a mean deviation of 0.0402 Å for one molecule and 0.0279 Å for the other. The carbazole planes are inclined to the benzene ring planes at dihedral angles of 58.3 (3) and 71.1 (3)° in the two molecules.